The role of mathematical and computer simulation in probabilistic thinking style development - Nikolayevna Dvoryatkina, Svetlana; Anzhelika Aleksandrovna Dyakina, Aleksandr Viktorovich Dobrin,; Shcherbatykh, Sergey Victorovich (Opción, 2019)
The main purpose of the article is theoretical substantiation, development and introduction into practice of teaching methods, means and forms of development of the probabilistic thinking style as a universal competency and a key structural component in the professional culture of a multi-skilled journalist via comparative qualitative research methods. As a result, the presented system of principles has made it possible to create a new didactic construct based on a dialogue of cultures. In conclusion, the principle of integrative learning seems also promising in holding advanced training courses, workshops, and training sessions for traditional media specialists.